The Earth as soundscape: a very sketchy portrait of a very noisy planet - Puppel, Stanisław (Scripta Neophilologica Posnaniensia, 2020)
The earth forms a gigantic sound theatre. The sound arena, as we may also call it, has been formed in a number of phases. They include the following: the phase of the formation of the natural sound arena (geophony), the formation of the bio sound arena (biophony/zoophony), the phase of the formation of the human sound arena (anthropophony), the phase of the formation of machine-produced sound arena (technophony). All of them are merged into the Earth’s soundscape. In ecological terms, technophony should be kept at a minimum if the Earth’s overall wellbeing is to be considered seriously.